Predictive factors of early progression after CAR T-cell therapy in relapsed/refractory diffuse large B-cell lymphoma - Vercellino, Laetitia; Di Blasi, Roberta; Kanoun, Salim; Tessoulin, Benoit; Rossi, Cedric; D'Aveni-Piney, Maud; Obéric, Lucie; Bodet-Milin, Caroline; Bories, Pierre; Olivier, Pierre; Lafon, Ingrid; Berriolo-Riedinger, Alina; et al. (Blood advances, 2020)
Chimeric antigen receptor (CAR) T-cell therapy has emerged as an option for relapsed/refractory aggressive B-cell lymphomas that have failed 2 lines of therapy. Failures usually occur early after infusion. The purpose of our study was to identify factors that may predict failure, particularly early progression (EP), within the first month after infusion. Characteristics of 116 patients were analyzed at the time of decision (TD) to use commercial CAR (axicabtagene ciloleucel, n = 49; tisagenlecleucel n = 67) and at the time of treatment (TT), together with total metabolic tumor volume (TMTV) at TT. With a median follow-up of 8.2 months, 55 patients failed treatment; 27 (49%) were early progressors. The estimated 12-month progression-free survival (PFS) and overall survival (OS) were 47.2% (95% confidence interval [CI], 38.0-58.6) and 67.0% (95% CI, 57-79), respectively. Univariate analyses for PFS and OS identified Eastern Cooperative Oncology Group Performance Status (ECOG PS) ≥2, stage III/IV disease, extranodal (EN) sites ≥2, elevated lactate dehydrogenase (LDH), increased C-reactive protein (CRP), high International Prognostic Index at TD and at TT, as well as increased CRP, bulky mass, and high TMTV at TT, as risk factors. Multivariate analyses for PFS, EP, and OS identified elevated LDH and EN sites ≥2 at TD and the same predictors at TT (ie, increased CRP, EN sites ≥2, and TMTV >80 mL). In summary, risk factors identified for early progression at TD and at TT were EN involvement (≥2 sites) and lymphoma burden (LDH, TMTV). •Forty-nine percent of relapses after CAR T-cell treatment in relapsed/refractory DLBCL occur within the first month.•Risk factors for early progression are extranodal sites ≥2, increased CRP, and high TMTV at the time of treatment. [Display omitted]